Analysis of Heavy Metals in Pigments Used in Makeup Tattoo - Seong Lee, Hui; Seung Choi, jung; Jin Baek, Dae; Ra Jeong, Mi (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study aims to provide basic material to establish safety sign standard and control standard of cosmetic tattoo pigment by analyzing heavy metal component of pigment used in cosmetic tattoo.Methods/Statistical analysis: The experiment analyzed heavy metal such as antimony(Sb), cobalt(Co), copper(Cu), lead(Pb), zinc(Zn), barium(Ba), tin(Sn) included in regulated item by applying safety standard of prohibition of use or content restriction of hazardous material since September 26, 2015 in accordance with â€œAct on Registration, Evaluation, Etc. of Chemicalâ€ simplemented by the Environment department on June 26, 2015.Findings: As a result of examining the contents of heavy metals in dyes and pigments used in cosmetic tattoo products, it was found that the total of 5products exceeded the reference value and found to be unsuitable for safety standards.Improvements/Applications: it requires marking of detailed compound ingredient and guidelines. There is a need for micro content analysis using precise measuring tool in the future.Â Â